2021
DOI: 10.1002/ctm2.312
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 ameliorates nitrogen mustard‐induced cutaneous inflammation by inactivating the NLRP3 inflammasome through the SIRT3–SOD2–mtROS signaling pathway

Abstract: Nitrogen mustard (NM) causes severe skin injury with an obvious inflammatory response, which is lack of effective and targeted therapies. Vitamin D3 (VD3) has excellent anti‐inflammatory properties and is considered as a potential candidate for the treatment of NM‐induced dermal toxicity; however, the underlying mechanisms are currently unclear. Cyclooxygenase‐2 (COX2; a widely used marker of skin inflammation) plays a key role in NM‐induced cutaneous inflammation. Herein, we initially confirmed that NM marked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 54 publications
2
34
0
Order By: Relevance
“…In addition, WBCs and the pro-inflammatory cytokines also contribute to reactive oxygen species (ROS) overproduction and oxidative damage [ 5 , 6 ]. Both pro-inflammatory cytokines and ROS are potential activators of nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome, which is consistent of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1, and promotes the maturation and release of pro-inflammatory cytokines (e.g., IL-1β and IL-18) [ [7] , [8] , [9] , [10] ]. Macrophages are the dominant inflammatory cells in the lungs, and play critical roles in sepsis-induced inflammation, oxidative stress and ALI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WBCs and the pro-inflammatory cytokines also contribute to reactive oxygen species (ROS) overproduction and oxidative damage [ 5 , 6 ]. Both pro-inflammatory cytokines and ROS are potential activators of nucleotide-binding domain-like receptor protein 3 (NLRP3) inflammasome, which is consistent of NLRP3, apoptosis-associated speck-like protein containing a CARD (ASC) and caspase-1, and promotes the maturation and release of pro-inflammatory cytokines (e.g., IL-1β and IL-18) [ [7] , [8] , [9] , [10] ]. Macrophages are the dominant inflammatory cells in the lungs, and play critical roles in sepsis-induced inflammation, oxidative stress and ALI [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these studies have demonstrated a positive feedback interaction between SIRT3 and PGC-1α, providing SIRT3/PGC-1α activation as a viable strategy for the intervention of DCM. Moreover, SIRT3 has been reported to be a crucial negative regulator of NLRP3 [40][41][42][43]. Mechanistically, SIRT3 deacetylates SOD2, leading to SOD2 activation, which impairs NLRP3 inflammasome assembly and activation [41].…”
Section: Discussionmentioning
confidence: 99%
“… 125 , 126 , 129 Vitamin D3 downregulated mitochondrial ROS and related participants, for example, cyclooxygenase‐2, superoxide dismutase 2, NOD‐like receptor family pyrin domain containing 3, caspase‐1, SIRT3, and interleukin‐1β. 130 Changes in mitochondrial proteins and functions were also noticed in pulmonary arterial hypertension (PAH) and COPD. 37 , 131 , 132 Disease‐specific proteins related to mitochondrial function were identified from proteomic profiles of lung cancer, PAH, and COPD clinically and experimentally.…”
Section: Clinical Significance Of Mitochondrial Functionmentioning
confidence: 99%
“… 127,128 Anticancer drugs inhibit the proliferation of lung cancer cells through targeting either mitochondrial bioenergetics, mitochondrial ROS production, or pyruvate dehydrogenase kinase activity (Figure 5C). 125,126,129 Vitamin D3 downregulated mitochondrial ROS and related participants, for example, cyclooxygenase‐2, superoxide dismutase 2, NOD‐like receptor family pyrin domain containing 3, caspase‐1, SIRT3, and interleukin‐1β 130 . Changes in mitochondrial proteins and functions were also noticed in pulmonary arterial hypertension (PAH) and COPD 37,131,132 .…”
Section: Clinical Significance Of Mitochondrial Functionmentioning
confidence: 99%